PERANCANGAN AGROEDUWISATA PADA KAWASAN DOLAN SAWAH - Borisman Halawa; Alfred Jansen Sutrisno (Kepariwisataan: Jurnal Ilmiah, 2026)
AbstractDolan Sawah is a restaurant that provides an agricultural view with a backdrop of rice fields and Mount Merbabu in Salatiga. This area has the potential to be developed as an agro-edutourism to optimize vacant land and increase educational and recreational values. This study aims to optimize this potential based on environmental conditions and visitor perceptions. This study uses an exploratory method with quantitative and qualitative approaches. Quantitative data include land biophysical conditions (organic C, Potassium, Phosphorus, soil pH), temperature, humidity, and thermal comfort (THI), while qualitative data include visitor perceptions and preferences. Data analysis uses descriptive analysis for biophysical conditions, Temperature Humidity Index (THI) calculations for thermal comfort, and a Likert scale for visitor perceptions and preferences. The results of the study indicate that the land that can be developed is 1,696.38 m² out of a total of ±105,890.7 m², with slightly acidic soil conditions and low to moderate nutrient content, and thermal comfort is predominantly uncomfortable during the day. Visitor perceptions of Dolan Sawah were positive, and there was high support for the development of agro-educational tourism. The conclusion is to optimize this potential by designing an agro-educational tourism landscape concept with the theme "Playful Agro-Educational Experience".Keywords: Agroeducational Tourism; Dolan Sawah; Landscape Design; Thermal Comfort; Visitor Perception AbstrakDolan Sawah merupakan restoran yang memberikan nuansa view pertanian dengan latar belakang persawahan dan Gunung Merbabu, Salatiga. Kawasan ini berpotensi dikembangkan sebagai agroeduwisata untuk mengoptimalkan lahan kosong serta meningkatkan nilai edukasi dan rekreasi. Penelitian ini bertujuan untuk mengoptimalkan potensi tersebut berdasarkan kondisi lingkungan dan persepsi pengunjung. Penelitian ini menggunakan metode eksploratif dengan pendekatan kuantitatif dan kualitatif. Data kuantitatif meliputi kondisi biofisik lahan (C-organik, Kalium, Fosfor, pH tanah), suhu, kelembaban, dan kenyamanan termal (THI), sedangkan data kualitatif berupa persepsi dan preferensi pengunjung. Data analisis menggunakan analisis deskriptif untuk kondisi biofisik, perhitungan Temperature Humidity Index (THI) untuk kenyamanan termal, serta skala Likert untuk persepsi dan preferensi pengunjung. Hasil penelitian menunjukkan bahwa lahan yang dapat dikembangkan sebesar 1.696,38 m² dari total ±105.890,7 m², dengan kondisi tanah agak masam dan unsur hara rendah hingga sedang, serta kenyamanan termal dominan tidak nyaman pada siang hari. Persepsi pengunjung tergolong baik terhadap Dolan Sawah serta dukungan tinggi terhadap pengembangan agroeduwisata. Kesimpulannya adalah mengoptimalkan potensi tersebut melalui perancangan konsep lanskap agroeduwisata yang bertema “Playful Agro-Education Experience."Kata Kunci: Agrowisata Edukatif; Dolan Sawah; Desain Lanskap; Kenyamanan Termal; Persepsi Pengunjung